2005
DOI: 10.1164/rccm.200502-230oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ductus Ligation on Cardiopulmonary Function in Premature Baboons

Abstract: Although a patent ductus arteriosus (PDA) increases fluid and protein efflux from the pulmonary vasculature in preterm infants (1, 2), a compensatory increase in pulmonary lymph flow appears to prevent pulmonary edema during the first 72 h after delivery in both premature animals (3, 4) and humans (5). However, a symptomatic left-to-right ductus shunt that persists beyond the first week of life increases the likelihood of edema formation and respiratory compromise. Several studies (performed in the presurfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
0
33
1
3
Order By: Relevance
“…Premature delivery and mechanical ventilation of preterm baboons have also been shown to increase proinflammatory cytokines/ chemokines (1,12,13). However, in studies we have previously reported, IL-6 and IL-8 expression did not seem to differ between control animals (with a PDA) and those with a surgically ligated ductus (14).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Premature delivery and mechanical ventilation of preterm baboons have also been shown to increase proinflammatory cytokines/ chemokines (1,12,13). However, in studies we have previously reported, IL-6 and IL-8 expression did not seem to differ between control animals (with a PDA) and those with a surgically ligated ductus (14).…”
Section: Discussionmentioning
confidence: 56%
“…A complete description of the details of animal care and the surgical procedures have been published elsewhere (1,12,14) (see also online data supplement for Refs. 1,12,14). Briefly, timed pregnant baboon (Papio papio) dams were delivered at 125 Ϯ 1 d gestation (full term ϭ 185 d) and their newborns were mechanically ventilated for 14 d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed oxygenation failure in the first 72 h but an improvement in lung compliance and pulmonary hemodynamics 1 week after the procedure. 28 …”
Section: Pda Ligation and Pulmonary Morbiditymentioning
confidence: 99%
“…Recent findings in premature baboons support the concept that surgical ligation may have a detrimental effect on lung function and growth. Although pharmacologic closure prevents the arrest in alveolar development caused by a PDA (19), no benefit on alveolar growth has been observed following surgical ligation (35,36).…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%